Novel Aspects of White Adipose Tissue Browning by Thyroid Hormones - Krause, Kerstin (Experimental and Clinical Endocrinology & Diabetes, 2019)
Thyroid hormones are essential for the full thermogenic capacity of brown adipose tissue. The thermogenic response of brown adipocytes to thyroid hormones is resulting from the synergistic interaction of thyroid hormones with the sympathetic nervous system. In recent years, evidence has been provided that thyroid hormones also induce the browning of white adipose tissues. This review will provide a brief overview about the recent findings regarding the effects of thyroid hormones on adipose tissue thermogenesis including central and peripheral regulation of white adipose tissue browning.
Keywords: thyroid hormone; adipose tissue; browning; thermogenesis